2012
DOI: 10.1100/2012/193213
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and Limitations of Real-Time Elastography for Prostate Cancer Detection: A Whole-Mount Step Section Analysis

Abstract: Objectives. To evaluate prostate cancer (PCa) detection rates of real-time elastography (RTE) in dependence of tumor size, tumor volume, localization and histological type. Materials and Methods. Thirdy-nine patients with biopsy proven PCa underwent RTE before radical prostatectomy (RPE) to assess prostate tissue elasticity, and hard lesions were considered suspicious for PCa. After RPE, the prostates were prepared as whole-mount step sections and were compared with imaging findings for analyzing PCa detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…For diffusion-weighted MRI (DWI), Langer et al demonstrated that all “invisible” tumours in DWI had predominant Gleason pattern 3 and showed sparse architecture on histology [26]. For RTE, we revealed similar results, since RTE visualises cancer due to the higher cell density compared to the normal surrounding tissue [13, 27]. Nearly all cancers missed on RTE in our study population with a significant tumour volume were also of sparse architecture and had predominant Gleason pattern 3.…”
Section: Physiology-histology: Normal Patterns False Positive Ansupporting
confidence: 61%
“…For diffusion-weighted MRI (DWI), Langer et al demonstrated that all “invisible” tumours in DWI had predominant Gleason pattern 3 and showed sparse architecture on histology [26]. For RTE, we revealed similar results, since RTE visualises cancer due to the higher cell density compared to the normal surrounding tissue [13, 27]. Nearly all cancers missed on RTE in our study population with a significant tumour volume were also of sparse architecture and had predominant Gleason pattern 3.…”
Section: Physiology-histology: Normal Patterns False Positive Ansupporting
confidence: 61%
“…In general, imaging of prostate cancer is limited by tumor volume (size) and grade, because cancers with a predominant Gleason pattern of 3 (i.e., Gleason score of 6 with 3 + 3 or of 7 with 3 + 4) are intermixed with normal glands and glands with dilated lumina (sparse tumors) [7,17,18]. Delongchamps et al [16] used a similar multiparametric MRI setting with an endorectal coil at 1.5 T and for prostate cancers with volumes greater than 0.2 cm 3 reported a sensitivity of 80% for the peripheral zone and 53% for the transitional zone, which are in concordance with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is a finding of a suspicious tumor of the prostate if a hardened area > 5 mm can be reproduced on two different planes [32]. For example, sensitivity of 9.7 % could be shown for prostate cancer with maximum diameters of 0 -5mm; 27 % for prostate cancer with maximum diameters of 6 -10mm; 70.6 % for prostate cancer with maximum diameters of 11 -20mm; and 100 % for prostate cancer with maximum diameters of > 20 mm [30].…”
Section: False-negative Changesmentioning
confidence: 91%
“…This type of histological tumor composition in generally found in prostate cancer with primary Gleason pattern 3 (G6 (3 + 3) or G7 (3 + 4)). Above G7 (4 + 3), USE sensitivity for prostate cancer detection is very high, since this cancer type is very compact as a rule (dense architecture) [30]. Since prostate cancer ≤ G7 (3 + 4) is considered insignificant, and significant if greater than G7 (4 + 3), USE particularly appears to be a possible technology to reduce the much-criticized over-diagnosis and over-treatment of this cancer [31].…”
Section: False-negative Changesmentioning
confidence: 99%
See 1 more Smart Citation